ROOTING OF ARAUCARIA MINI-CUTTINGS IN DIFFERENT ENVIRONMENTS AND SUBSTRATES - Cipriani, Vânia Beatriz; Aguiar, Natália Saudade; Duarte, Manoela Mendes; Gabira, Mônica Moreno [UNESP]; Benedito, Débora Caroline Defensor; Wendling, Ivar (My University, 2024)
Araucaria is a native conifer, with high economic importance, especially in the southern region of the Brazil. Considering the difficulties of producing clonal plants of the species, the objective of the study was to determine the influence of different environments and substrates on root formation of Araucaria angustifolia minicuttings. Orthotropics shoots were collected in a mini clonal garden. Minicuttings were prepared with 10 ± 1 cm in length, keeping 1/3 of the needles, and immersed in a hydroalcoholic solution of 3,000 mg L-1 of indolbutyric acid for 10 seconds. Then they were planted in 210 cm3 tubes, testing four different substrates, which are, based on pine bark, vermiculite and charcoal (S1); based on pine bark and vermiculite (S2); based on pine bark, peat and coconut fiber (S3) and based on pine bark, vermiculite, charcoal and carbonized rice husk (S4). These minicuttings were maintained in three different environments for rooting: Automated Greenhouse (CVA) with 80% reduction in luminosity and mist irrigation, Simple Greenhouse House (CVS) with 84% reduction in luminosity and microsprinkler irrigation, and Mini-tunnel (EST) with 90% light reduction and micro sprinkler irrigation. After 120 days, minicuttings survival and rooting were determined. CVA provided better rooting of minicuttings, whereas EST resulted in high mortality and no root formation. There was no influence of the substrates on the evaluated variables. Thus, the use of greenhouses with automated irrigation by misting is recommended for rooting araucaria minicuttings, regardless of the substrate used, although overall rooting rates are not yet considered viable.
Enraizamento de miniestacas de araucária em diferentes ambientes e substratos
Keywords: Araucaria angustifolia; brazilian pine; casa de vegetação; greenhouse; pinheiro brasileiro; propagação vegetativa; rhizogenesis; rizogênese; vegetative propagation